Sistem Pakar Menggunakan Metode Naïve Bayes dan Certainty Factor untuk Mendeteksi Hama pada Tanaman Alpukat Berbasis Web - Ferriza Tyar; Muhammad Iwan Wahyuddin (KITA Institute, 2022)
Avocad (Persea americana) is a table fruit-producing plant of the same name. This plant comes from Mexico and Central America as a garden plant in other tropical areas of the world. In Indonesia itself, avocados are widely found because of the tropical climate, then people also like avocados because there are many choices from various food and beverage ingredients. Lack of attention to the cultivation and breeding of avocados makes the yields less good, and not optimal. so the author conducted this research in the hope that the yield and breeding of avocado plants can be maximized. This expert system was built using Web-based programming. The method applied is Naïve Bayes, which is a method that uses statistics and probability in predicting the chances of avocado plants having growth disorders based on the presence of pests (worms) in avocado plants.